2002
DOI: 10.1152/ajpendo.00266.2002
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and cardiorespiratory responses to “the lactate clamp”

Abstract: To evaluate the hypothesis that precursor supply limits gluconeogenesis (GNG) during exercise, we examined training-induced changes in glucose kinetics [rates of appearance (R a) and disappearance (Rd)], oxidation (R ox), and recycling (Rr) with an exogenous lactate infusion to 3.5-4.0 mM during rest and to pretraining 65% peak O 2 consumption (V O2 peak) levels during exercise. Control and clamped trials (LC) were performed at rest pre-(P RR, PRR-LC) and posttraining (POR, POR-LC) and during exercise pre-(P R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(123 citation statements)
references
References 42 publications
4
118
0
Order By: Relevance
“…We observed a significant decrease of blood glucose concentration during exercise from 5.0 to 4.2 mM after 4 h. A decrease of similar extent has been reported by others, albeit in humans performing exercise at higherintensity levels, up to 65% V O 2 max (15,28,29,44,45). In those studies, subjects were studied 7.5 h after their last meal, and exercise commenced 12 h following completion of their evening meal.…”
Section: H Enrichment In Body Water and At C-5 Of Glucose And Estimatsupporting
confidence: 89%
See 1 more Smart Citation
“…We observed a significant decrease of blood glucose concentration during exercise from 5.0 to 4.2 mM after 4 h. A decrease of similar extent has been reported by others, albeit in humans performing exercise at higherintensity levels, up to 65% V O 2 max (15,28,29,44,45). In those studies, subjects were studied 7.5 h after their last meal, and exercise commenced 12 h following completion of their evening meal.…”
Section: H Enrichment In Body Water and At C-5 Of Glucose And Estimatsupporting
confidence: 89%
“…Differences in physiological state could also explain the difference between our findings (obtained during prolonged low-intensity exercise) and those of previous studies (obtained in subjects under resting conditions). Recently, Miller and colleagues (28,29) studied the effect of hyperlactatemia due to lactate infusion (lactate clamp) in healthy volunteers at rest and under exercise at moderate and high intensity. In contrast to our observations, they found a decrease in glucose R a during lactate infusion under exercise.…”
mentioning
confidence: 99%
“…In the process of shuttling between sites of production and removal, lactate exerts profound effects on fat and CHO metabolism. Because lactate is a preferred fuel over glucose in the heart [69], working muscle [4,70,71] and brain [72], hyperlactatemia affects glucose uptake and oxidation by substituting for pyruvate and lactate produced from glycolysis in widely dispersed tissues. Lactate is oxidized via the mitochondrial lactate oxidation complex (mLOC) comprising the monocarboxylate transporter-1 (MCT1), its chaperone (CD147), mitochondrial lactate dehydrogenase (mLDH), and cytochrome oxidase (COx) [73,74].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that an increase in blood lactate induced changes in the concentration of blood catecholamine and whole-body glucose metabolism (13)(14)(15). These findings indicate the role of lactate as an index for monitoring energy metabolism, and that increase in lactate affects energy metabolism.…”
Section: Discussionmentioning
confidence: 56%